Analisis Pengaruh Foreign Direct Investment dan Pendapatan Per Kapita terhadap Pertumbuhan Ekonomi di Indonesia - Christo Fanre Parlindungan Sembiring; Ida Bagus Putu Purbadharmaja (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Economic growth is a key indicator for assessing the success of a country’s development, including Indonesia. This study aims to analyze the effect of Foreign Direct Investment (FDI), per capita income, and technology budget as a moderating variable on Indonesia’s economic growth during the 1993–2023 period. Using annual panel data over 31 years, the analysis employed panel data regression and Moderated Regression Analysis (MRA) to examine the relationships among variables. The results show that both FDI and per capita income have a positive and significant influence on national economic growth. Furthermore, the technology budget acts as a moderating factor that strengthens the relationship between FDI and economic growth, showing a positive and significant coefficient. These findings indicate that increasing foreign investment and per capita income are key drivers of Indonesia’s economic expansion. Moreover, government support through technology budget allocation enhances national economic competitiveness by fostering innovation and production efficiency. Therefore, policies that promote a conducive investment climate, income equality, and technological advancement should be prioritized to ensure sustainable and inclusive economic growth in Indonesia.